Implementasi Algoritma Round Robin Pada Sistem Penjadwalan Mata Kuliah (Studi Kasus: Universitas Muhammadiyah Bengkulu) - Ardi Wijaya; Gunawan Gunawan (Universitas PGRI Semarang, 2018)
Subjects scheduling is an important routine for teaching and learning process in every semester. These teaching and learning processes involve all students and lecturers, so the arranged subjects scheduling should be able to facilitate the interests both of lecturers and students. If some constraints in scheduling process are not counting well, it will difficult to do subjects scheduling. The constraints are the number of available: subjects, classes, times, and lecturers. The current subjects scheduling process is not efficient. Manual input activity make the scheduling process become complicated and slow. Therefore it need an application which can solve scheduling problems which can be used to arrange the subjects in every departments (majors) in UMB, so that distribution of subjects can be divided equally everyday. This problem required an application with a model that can solve scheduling complexities which adjust with the predefined constraints. Round Robin Algorithm is able to make this scheduling process faster and more efficient, so that some items in scheduling process no need to be inserted (input) repeatedly.